EDUKASI LEAFLET SEBAGAI UPAYA MENINGKATKAN PENGETAHUAN DAN KEPATUHAN IMUNISASI DASAR - Talitha Cahya Kemala Dewi; Indah Permatasari (LPPM Universitas Abdurrab, 2026)
Introduction: To build and strengthen immunity, immunization is a crucial step. It allows a person to avoid disease or only experience its symptoms. However, parental knowledge and compliance with basic immunization remain problematic in some places. A national report stated that the achievement of complete basic immunization in 2020 was around 83.3%, still below the national strategic target. Ignorance about the benefits, schedule, and side effects of vaccines is often a major factor causing low coverage. Education through leaflets, which is an easily accessible method and has been proven effective in several controlled studies, can improve knowledge and behavior related to vaccination, potentially encouraging parents to receive basic vaccinations. Objective: The purpose of this study was to determine significant differences between maternal knowledge and compliance with basic immunization before and after being provided with health education using leaflets. Method: This study used a quasi-experimental design with a pretest-posttest model without a control group, in the working area of ​​the Bambu Apus Community Health Center. A total of 44 mothers with babies aged 0–9 months and who met the inclusion criteria participated in the study and underwent the entire series of leaflet media education. Data were collected using a knowledge questionnaire and a compliance questionnaire. Results: The results of the Wilcoxon test statistical analysis for maternal knowledge obtained a p-value score <0.001, while the results of maternal compliance in administering immunizations with a statistical test using McNemar showed a p-value score of 0.016, which means there is a significant difference between maternal knowledge and compliance before and after being given health education using leaflets regarding basic immunizations. Recommendation: It is hoped that immunization programs at the community level can integrate the use of leaflets as supporting media to increase understanding and encourage maternal compliance in carrying out basic immunizations in children